Diverging metabolic programmes and behaviours during states of starvation, protein malnutrition, and cachexia. Issue 6 (28th September 2020) - Olson, Brennan; Marks, Daniel L.; Grossberg, Aaron J.
Abstract: Background: Our evolutionary history is defined, in part, by our ability to survive times of nutrient scarcity. The outcomes of the metabolic and behavioural adaptations during starvation are highly efficient macronutrient allocation, minimization of energy expenditure, and maximized odds of finding food. However, in different contexts, caloric deprivation is met with vastly different physiologic and behavioural responses, which challenge the primacy of energy homeostasis. Methods: We conducted a literature review of scientific studies in humans, laboratory animals, and non‐laboratory animals that evaluated the physiologic, metabolic, and behavioural responses to fasting, starvation, protein‐deficient or essential amino acid‐deficient diets, and cachexia. Studies that investigated the changes in ingestive behaviour, locomotor activity, resting metabolic rate, and tissue catabolism were selected as the focus of discussion. Results: Whereas starvation responses prioritize energy balance, both protein malnutrition and cachexia present existential threats that induce unique adaptive programmes, which can exacerbate the caloric insufficiency of undernutrition. We compare and contrast the behavioural and metabolic responses and elucidate the mechanistic pathways that drive state‐dependent alterations in energy seeking and partitioning. Conclusions: The evolution of energetically inefficient metabolic and behavioural responses to protein malnutrition and cachexia reveal a hierarchy of metabolic priorities governed by discrete regulatory networks.